Enhancement of Antioxidant and Anti-Glycation Properties of Beeswax Alcohol in Reconstituted High-Density Lipoprotein: Safeguarding against Carboxymethyllysine Toxicity in Zebrafish - Kyung-Hyun Cho; Seung-Hee Baek; Hyo-Seon Nam; Ashutosh Bahuguna (Antioxidants, 2023)
The antioxidant and anti-inflammatory abilities of beeswax alcohol (BWA) are well reported in animal and human clinical studies, with a significant decrease in malondialdehyde (MDA) in the blood, reduced liver steatosis, and decreased insulin. However, there has been insufficient information to explain BWAs in vitro antioxidant and anti-inflammatory activity owing to its limited solubility in an aqueous buffer system. Herein, three distinct reconstituted high-density lipoproteins (rHDL) were prepared with palmitoyloleoyl phosphatidylcholine (POPC), cholesterol, apolipoprotein A-I (apoA-I), and BWA at molar ratios of 95:5:1:0 (rHDL-0), 95:5:1:0.5 (rHDL-0.5), and 95:5:1:1 (rHDL-1) and examined for antioxidant and anti-glycation effects. A rHDL containing BWA, precisely rHDL-1, displayed a remarkable anti-glycation effect against fructose (final 250 mM), induced glycation of HDL, and prevented proteolytic degradation of apoA-I. Also, BWA incorporated rHDL-0.5, and rHDL-1 displayed substantial antioxidant activity by inhibiting cupric ion-mediated low-density lipoprotein (LDL) oxidation. In contrast to rHDL-0, a 20 and 22% enhancement in ferric ion reduction ability (FRA) and paraoxonase (PON) activity was observed in HDL treated with rHDL-1, signifying the effect of BWA on the antioxidant activity enhancement of HDL. rHDL-1 efficiently inhibits Nε-carboxylmethyllysine (CML)-induced reactive oxygen species (ROS) generation and apoptosis in zebrafish embryos, consequently improving embryo survivability and developmental deformities impaired by the CML. The dermal application of rHDL-1 to the CML-impaired cutaneous wound of the adult zebrafish inhibited ROS production and displayed potent wound-healing activity. Conclusively, incorporating BWA in rHDL significantly enhanced the anti-glycation and antioxidant activities in rHDL via more stabilization of apoA-I with a larger particle size. The rHDL containing BWA facilitated the inherent antioxidant ability of HDL to suppress the CML-induced toxicities in zebrafish embryos and ameliorate CML-aggravated chronic wounds in adult zebrafish.